Principles of Cancer Reconstructive Surgery - Butler, Charles E.; Fine, Neil A.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2008)
Principles of Cancer Reconstructive Surgery is a reference text for medical and surgical oncologists, radiation oncologists, family practice physicians and dermatologists, providing an overview for reconstructive procedures. Interested residents, medical students and health care professionals may find this to be a resource for information on reconstructive plastic surgery. It is designed to educate those involved with the management of cancer patients and serve as a reference source. The disease specific format facilitates quick reference for those who wish to focus on a single body area or disease. The most commonly occurring cancers, breast, melanoma, head and neck, are covered in an overview chapter and in greater detail in individual chapters. This volume includes nearly 300 color illustrations and the 7x10 format give the reader excellent detail and clarity.
Plastic Surgery -- The Principles of Cancer Reconstruction -- Breast Reconstruction -- Breast Reconstruction -- Breast Reconstruction -- Skin Cancer and Reconstruction -- Lip, Cheek, and Scalp Reconstruction -- Reconstruction of Mandible, Maxilla, and Skull Base -- Pharynx, Cervical Esophagus, and Oral Cavity Reconstruction -- Concepts in Nasal Reconstruction -- Extremity Reconstruction -- Abdominal Wall Tumors and Their Reconstruction -- Reconstruction of the Intra-Abdominal Pelvis and the Perineum -- Management of Chemotherapeutic Agent Extravasation and Radiation Therapy Adverse Effects.
Keywords: Surgical oncology; Plastic surgery; Oncology .; Surgical Oncology; Plastic Surgery; Oncology